Exploring the Integration of Socio-Emotional Learning Elements in Mother-Tongue Textbooks for Grades I–V in North Macedonia - Zenki-Dalipi, Arbresha; Ramadani Rasimi, Teuta; Adili, Bujar (Scientia Publica Media, 2026)
Social and emotional learning (SEL) represents a fundamental dimension of holistic education, fostering students’ emotional literacy, empathy, and interpersonal competence as essential outcomes of schooling. The study employed a quantitative content analysis to examine the extent to which elements of SEL were represented in selected Albanian language textbooks used in the first, second, third, fourth, and fifth grades of basic education. The analysis focused on identifying explicit and implicit SEL components within textual and visual content, drawing upon the Collaborative for Academic, Social, and Emotional Learning (CASEL, 2020) framework as the analytical lens. A total of five textbooks approved by the Ministry of Education and Science were purposively selected based on their mandatory use in public schools during the 2021–2025 academic period. The units of analysis consisted of all lessons, reading texts, and accompanying illustrations. Each content item was examined for the presence of at least one of the five core SEL competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. The identification process followed a structured coding protocol developed for this study, and all data were entered into Excel and analyzed using descriptive statistics (frequencies and percentages) to determine the proportion of SEL elements across grade levels and literary genres. This methodological approach ensured both descriptive and interpretative validity, providing insights into how SEL competencies were integrated into language learning materials and to what extent they reflected the principles of holistic education. The findings revealed a moderate presence of SEL elements, with social awareness and relationship skills more prominent, suggesting the need for a more balanced integration of all competencies in future textbook revisions.